Dielectric spectroscopy for monitoring human pancreatic islet differentiation within cell-seeded scaffolds in a perfusion bioreactor system. Issue 18 (21st September 2015) - Daoud, J.; Heileman, K.; Shapka, S.; Rosenberg, L.; Tabrizian, M.
<x xml:space="preserve">Abstract</x> Herein, we describe a platform for dielectric spectroscopy monitoring of scaffold-embedded human pancreatic islet differentiation within a perfusion bioreactor.